Lutein and Zeaxanthin Content in Milling Fractions of Selected Wheat Species and Varieties - Lacko-Bartošová, Magdaléna; Leváková, Ľudmila (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Lutein and its isomer, zeaxanthin, belong to a class of carotenoids called xanthophylls. They are the main carotenoids in cereal grains. A number of human epidemiological and clinical studies have shown that their intake is associated with reduced incidence of age-related macular degeneration, the leading cause of irreversible blindness in elderly people, and cataracts. In addition, lutein may have protective benefits against skin cancer and may also help to prevent cardiovascular diseases. The objective of the present study was to evaluate lutein and zeaxanthin content in selected varieties of wheat species produced in organic farming system and their distribution in milling fractions. A field stationary experiment was established at the Research Experimental Station Dolná Malanta in western Slovakia, during the years 2013–2015. The significantly highest average lutein content was detected in bran fraction (2.546 μg/g dry weight) and the lowest in flour (1.675 μg/g dry weight). Among wheat species, the significantly highest content of lutein was achieved in the bran of Triticum monococcum L. (5.080 μg/g dry weight). The highest average concentrations of lutein were observed in the variety Franckenkorn of Triticum spelta L. (2.706 μg/g dry weight), particularly in bran fraction. In the case of zeaxanthin, the significantly highest content was determined in whole grain of Triticum monococcum (0.193 μg/g dry weight). No significant differences in the zeaxanthin content between milling fractions were determined. Triticum monococcum was the most important source of carotenoids, followed by Triticum spelta and Triticum dicoccon